Pathogenesis of Chiari II Malformation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Ependymal vimentin immunoreactivity was studied in necropsy specimens of brains and spinal cords of 14 patients with Chiari II malformations and 2 with congenital aqueductal stenosis without Chiari malformation at Cedars-Sinai Medical Center and UCLA School of Medicine, Los Angeles, CA.